(untitled) (International Journal of Engineering and Computer Science, 2015)
Grid approach in wireless sensor network is a key technique for extending the life time of a network by reducing energy consumption. This also increases network’s capacity, reduces the routing overhead and makes it more scalable when nodes are in large number. Clustering in wireless adhoc network is a key technique for reducing the energy consumption which increases the network lifetime, capacity. Scalability of network is increase by increasing the no of nodes. In section two there are no. In this paper we will study about grid based network and cluster based network and discuses about which one is more efficient to make energy consumption more considerable.